2017
DOI: 10.4236/ajps.2017.83043
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Action Strategy of Two Stresses, Salinity and Cu++ on Growth, Metabolites and Protein Pattern of Wheat Plant

Abstract: The response of wheat plants to different osmotic stress levels varied among the different organs root, shoot and spike and the situation of these organs with application of two Cu ++ levels 5 mM and 25 mM as CuSO 4 . The sensitivity of root organ was related with reduction in fresh, dry matter and length. This resulted from reduction of soluble sugar reflected a reduction in water uptake and K + content of the cell sap. In the moderate organ spike, the reduction in fresh, dry matter and length were concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It has been demonstrated that an excess of Cu 2+ can inhibit the growth of young seedling, root elongation and cause damage to root epidermal cells and root cell membranes [33] [34]. The differential effect of Cu 2+ on root and shoot growth could be accounted for by the fact that Cu 2+ is accumulated mainly in roots and to a minor extent in shoots [13] [35]. In our study, an interesting point was also reported, that the role of Cu 2+ as a fertilizer was more obvious than its toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that an excess of Cu 2+ can inhibit the growth of young seedling, root elongation and cause damage to root epidermal cells and root cell membranes [33] [34]. The differential effect of Cu 2+ on root and shoot growth could be accounted for by the fact that Cu 2+ is accumulated mainly in roots and to a minor extent in shoots [13] [35]. In our study, an interesting point was also reported, that the role of Cu 2+ as a fertilizer was more obvious than its toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the effect of the pH of the medium and Cu 2+ concentration was examined in order to optimize the evaluation of Cu 2+ tolerance in vitro. Hamdia et al (2017) [13] showed that response of wheat plants to different osmotic stress levels varied among the different organs root, shoot and spike and the situation of these organs with application of two Cu 2+ levels 5 mM and 25 mM as CuSO 4 . Data also showed further stimulatory effect on growth parameters by Cu 2+ applications with either concentration (7.5 mM or 25 mM).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations